McCullough and Berglund on mastering advanced Git - McCullough, Matthew (Matthew J.); Berglund, Tim.; Safari eBooks ([S.l.] : O'Reilly Media, 2012)
"Go beyond the basics and take Git to a higher level of productivity. If you're familiar with this popular distributed revision control system (DVCS), Mastering Advanced Git will help you leverage Git's powerful yet underused advanced features."--Resource description page.
Title from title screen.
Publication information from end credits.
Presenters, Matthew McCullough, Tim Berglund.
Keywords: Git (Computer file); Electronic data processing -- Distributed processing; Software engineering; Open source software; Electronic books